Parent involvement that supports children academically and promotes the development of independence - Loomans, Michelle G.S. (My University, 2014)
A significant body of research exists connecting parent involvement to the academic success of a child. This research explored practical ways to encourage and remove barriers to that involvement while continuing to foster the child's independence in the second plane of development. Participants in the research were members of an upper elementary class of 4th and 5th grade students in an urban public Montessori school in the Midwest. The researcher, a Montessori teacher, studied ways to integrate Montessori's ideas of developing independence with the conventional understanding of the importance of parent involvement. The author developed tools to encourage parent involvement by all parents and then asked whether the tools promoted academic success as well as independence. Data was collected through tracking work completion, parent participation in monitoring work-completion, parent feedback surveys, a parent interview and anecdotal records. The research showed that many parents were able to support their child's academic success with an unfamiliar curriculum, like Montessori, if they understood their role was to provide accountability, support in time management and support in workload management. The research also showed that for those families who are English Language Learners or without access to email, supporting their children academically was more challenging. Additional research needs to be done on developing tools to break down barriers for the ELL families as well as families without access to email.
Plan B Paper. 2014. Master of Science in Education- Montessori--University of Wisconsin-River Falls. Teacher Education Department. 53 leaves. Includes bibliographical references (leaves 49-53).
Keywords: Montessori method of education; Education, Elementary--Parent participation